Beyond Religious Habituation: Internalizing Islamic Educational Philosophy Values in Elementary Moral Education - Iqbal Amar Muzaki; Amirudin Amirudin; Hinggil Permana; Taufik Mustofa; Nurulwahidah Fauzi (J-PAI: Jurnal Pendidikan Agama Islam, 2026)
This research identifies a significant gap between the taught values of Islamic Educational Philosophy and students' reflective internalization in daily behavior within Islamic elementary schools. Despite the consistent implementation of Islamic educational practices, the internalization process of core values, namely Tawhid (oneness of God), Adab (etiquette/morality), and Amanah (trustworthiness), has not yet fully reached the stage of deep reflection or behavioral consistency outside the school environment. Using a qualitative design with an interpretative phenomenological approach, this study explores the lived experiences of principals, Islamic Education (PAI) teachers, classroom teachers, students, and parents across several Islamic elementary schools in Karawang. Data were gathered through in-depth interviews, participant observation, and documentary studies. Analysis followed the Miles and Huberman model, utilizing triangulation of sources, techniques, and time, alongside participant validation. The findings reveal that while Islamic educational values are integrated into the curriculum and school culture, their internalization requires three strategic components: (1) A reflective learning approach that transcends mere habituation; (2) Authentic moral modeling from educators; and (3) Synergetic collaboration between schools, families, and the community as a supporting ecosystem. The contribution of this research is the development of an operational framework for internalizing Islamic educational philosophy that integrates theological dimensions, reflective pedagogy, and environmental support, moving beyond ritualistic habituation. These findings are relevant for the development of value-based character education policies at the primary level in Indonesia.